Improvement of CNN model using integration of multimodal MRI sequences and multilevel fusion to enhance performance for brain tumor classification - Ade Umar Ramadhan; Shofwatul Uyun (International Journal of Advances in Intelligent Informatics, 2026)
The prevalence of brain tumors has been increasing annually, and headaches, a common initial symptom, represent the most common manifestation. However, there is a paucity of research on effective methods of assessing brain tumors. This study proposes a novel approach by introducing various modality fusion techniques based on their fusion levels, which are then categorized into four groups: single-modal, data-level fusion, feature-level fusion, and multilevel fusion. A total of 51 combinations are designed to evaluate the efficacy of these fusion techniques and modality configurations. The experiments used a BraTS2021, which comprises four magnetic resonance imaging (MRI) sequences (flair, t1, t1ce and t2). Initially, the image was pre-processed, encompassing data selection, conversion, and normalization. Subsequently, it was input into a 13-layer CNN architecture for feature extraction. Classification was facilitated by a soft voting method in ensemble learning, incorporating support vector machine (SVM), k-nearest neighbor (KNN), logistic regression, random forest, and decision tree algorithms. The predictive efficacy of the model was rigorously assessed through a comprehensive suite of metrics, prominently featuring accuracy, AUCROC, AUCPR, Cohen's Kappa, and MCC. The results indicate that multilevel fusion exhibits optimal performance, with an average accuracy of 95.84%, followed by feature-level fusion and data-level fusion, at 95.12% and 94.77%, respectively. The optimal fusion technique was identified as the combination with the FF configuration (1,2),3,4), producing an accuracy of 96.62%. The best-model combination proposed exhibited an accuracy difference of nearly 6% from the baseline model, underscoring the efficacy of the proposed approach. These empirical results establish a robust baseline for future investigations into sophisticated fusion architectures across hierarchical integration levels.